Antimicrobial evaluation of bismuth subsalicylate nanoparticles synthesized by laser ablation against clinical oral microorganisms. (February 2023) - Reyes-Carmona, Lorena; Camps, Enrique; Campos-González, Enrique; Mercado-Celis, Gabriela; Cervantes-Garduño, Alejandra; Pérez-Ibarra, Ezequiel A.; Álvarez-Chimal, Rafael; Rodil, Sandra E.; Almaguer-Flores, Argelia
Graphical abstract: Bismuth subsalicylate nanoparticles (BSS-NPs) were synthesized by laser ablation of solids in liquids. Their inhibitory capacity against subgingival microorganisms taken from patients with periodontal disease was tested and the bacterial identification by 16S rRNA sequencing was performed. Highlights: Bismuth subsalicylate nanoparticles (BSS-NPs) were synthesized by laser ablation. The nanoparticles maintained the physicochemical properties of BSS. BSS-NPs exhibited antimicrobial activity against periodontal microorganisms. BSS-NPs inhibited relevant subgingival bacteria from periodontitis patients. Abstract: Nowadays, nanotechnology can be useful to generate novel therapeutic compounds with antimicrobial properties for the treatment of different oral infections, such as periodontal diseases. In this work, the antibacterial activity of bismuth subsalicylate nanoparticles (BSS-NPs) synthesized by laser ablation of solids in liquids (LASL) was evaluated against microorganisms taken from subgingival biofilm samples of patients with periodontal disease. The physicochemical characterization of the BSS-NPs was performed using different techniques, such as Ultraviolet–Visible Spectroscopy (UV–Vis); X-Ray Diffraction (XRD); Transmission Electron Microscopy (TEM) and Fourier Transform Infrared Spectroscopy (FT-IR). The evaluation of the antibacterial activity of the BSS-NPs (16.6 µg/mL) against the oral clinical samples, was performed using the colony-forming unit assay. In addition, 16S rRNA sequencing was used to identify sensitive and resistant bacterial genera to the BSS-NPs. The characterization results showed that the synthesized BSS-NPs by laser ablation of solids in liquids maintained the triclinic crystallographic structure, and the vibrational modes of the functional groups of bismuth subsalicylate. Moreover, BSS-NPs presented a quasi-spherical shape, an average size of 4 nm, and water-suspended stability for up to 170 days. Regarding the antimicrobial activity, more than 30 % of the total cultivable bacteria from the oral biofilm samples were inhibited when exposed to BSS-NPs. In addition, sensitive microorganisms to the BSS-NPs such as Aggregatibacter, Streptococcus, Veillonella, Eikenella, Peptostreptococcus, Eubacterium, Prevotella, Selenomonas, Haemophilus, Filifactor, and others, were identified by bioinformatic analysis of 16S rRNA sequencing. Therefore, BSS-NPs have the potential for being used as a new alternative antimicrobial in the treatment of periodontal diseases, reducing the indiscriminate use of antibiotics and preventing the increase of antibiotic resistance.